2017
DOI: 10.11604/pamj.2017.27.185.9098
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wetting ability of five new saliva substitutes on heat-polymerized acrylic resin for retention of complete dentures in dry mouth patients: a comparative study

Abstract: IntroductionThe aim of this study was to evaluate & compare the wetting ability of five saliva substitutes & distilled water on heat-polymerized acrylic resin. Contact angle of the saliva substitute on denture base can be taken as an indicator of wettability. Good wetting of heat-polymerized acrylic resin is critical for optimum retention of complete dentures.MethodsTwo hundred & forty samples of heat-polymerized acrylic resin were fabricated using conventional method. 240 samples divided into 6 groups with 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
1
0
0
Order By: Relevance
“…The contact angle of Aqwet showed low angle indicating more wettability on heat-cured polymerized acrylic resin. This result is similar to the studies conducted by Sharma and Chitre, 10 Bikash and Seema, 12 and Mohsin et al, 13 showed that Aqwet saliva substitutes containing thickening agents for increased moistening, lubrication, and longer relief of surface of the oral cavity in patients with xerostomia so it helps for the retention of the denture.…”
Section: Discussionsupporting
confidence: 89%
“…The contact angle of Aqwet showed low angle indicating more wettability on heat-cured polymerized acrylic resin. This result is similar to the studies conducted by Sharma and Chitre, 10 Bikash and Seema, 12 and Mohsin et al, 13 showed that Aqwet saliva substitutes containing thickening agents for increased moistening, lubrication, and longer relief of surface of the oral cavity in patients with xerostomia so it helps for the retention of the denture.…”
Section: Discussionsupporting
confidence: 89%
“…Um dos critérios para avaliação do grau de umedecimento proporcionado pelas formulações de saliva é o ângulo de contato que pode sugestionar como seria a interação da saliva artificial com as superfícies da cavidade bucal ou que estão inseridas nela, como as próteses dentárias (Manosroi et al, 2020;Mohsin et al, 2017;Qureshi, 2022). Os ângulos de contato avaliados entre as soluções de inhame e os matérias avaliados (resina acrílica e Co-Cr alloy) por a Park et al (2010) foram menores que 90°.…”
Section: Autor/ Anounclassified